Pengaruh rasio tepung Garut hasil HMT dan xanthan gum terhadap daya serap air dan cooking loss mi laksa - Nuri Arum Anugrahati; Celine Margaretha Yudianto (AGROINTEK, 2022)
Laksa noodles are noodles made from rice flour. The texture of laksa noodles is rigid and they have a high cooking loss. Cooking loss of laksa noodles can be minimized by modifying of arrowroot starch with heat moisture treatment (HMT) and by adding of xanthan gum. The objectives of this research were to determine the effect of the ratio of rice flour:HMT arrowroot starch and also the concentration of xanthan gum on water retention and cooking loss of laksa noodles. In this research rice flour substituted with HMT modified arrowroot starch (100: 0, 90:10, 80:20, and 70:30) followed by added xanthan gum (1 %, 1.5 %, and 2 %). The experimental design of this research was a Completely Randomized Design with two factors. The result showed that the substitution of HMT arrowroot starch decreases laksa noodles' water retention on each xanthan gum concentration. The highest water retention was found with rice flour:HMT arrowroot (90:10) and 2 % xanthan gum. All ratios of rice flour:HMT arrowroot and 1-2 % xanthan gum of laksa noodles give lower cooking loss than commercial laksa noodles. Substitution of rice flour with HMT arrowroot with 1,5-2 % xanthan gum gives lower hardness but provides higher cohesiveness and adhesiveness of laksa noodles compared to control. The addition of 1,5 % xanthan gum could increase water retention of laksa noodles. The higher concentration of xanthan gum gives the lower the cooking loss of laksa noodles. Substitution of rice flour with HMT arrowroot with 1.5-2 % of xanthan gum could reduce hardness but increase the cohesiveness and adhesiveness of laksa noodles. The best laksa noodle is made by rice flour:HMT arrowroot 70:30 and 1.5 % xanthan gum based on its lowest cooking loss.